2020
DOI: 10.1101/2020.06.08.140244
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cross-sectional evaluation of humoral responses against SARS-CoV-2 Spike

Abstract: 42 43 Word Count for Summary: 168 44 45 Word Count for the Body of the Text: 1149 46 47 SUMMARY 48 The SARS-CoV-2 virus is responsible for the current worldwide coronavirus disease 2019 49 (COVID-19) pandemic, infecting millions of people and causing hundreds of thousands of 50 deaths. The Spike glycoprotein of SARS-CoV-2 mediates viral entry and is the main target for 51 neutralizing antibodies. Understanding the antibody response directed against SARS-CoV-2 is 52 crucial for the development of vaccine, thera… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
76
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 39 publications
(88 citation statements)
references
References 35 publications
11
76
0
1
Order By: Relevance
“…However, the most striking observation comes from the comparison of the 3 rd and 4 th quartile (70 to 84 and 85 to 114 days after symptoms onset, respectively), where a marked decrease in the mean OD values (significative mean OD decrease of -0.486 from 1.321 ± 0.720 to 0.835 ± 0.670, representing a 36.8% decrease with p-value of 0.0052) and an even more pronounced decrease in median values (median OD decreases from 1.411 (IQR 1.52) to 0.411 (IQR 1.15) representing a 70.1% decrease) were observed. Altogether, these observations are in agreement with recent studies reporting a decrease in anti-RBD responses and neutralization activity in the plasma of convalescent donors a few weeks after symptoms resolution (19)(20)(21)(22) Interestingly, the decrease in mean and median OD values during a period of about 20 days (considering the mean and median of 3 rd and 4 th quartiles, both of 76 and 95 days respectively) is reminiscent of the plasma IgG half-life of 21 days (23), suggesting that de novo synthesis of anti-RBD antibodies stopped between the 3 rd and 4 th quartiles in all CCP donors. This time frame is consistent with the first wave of a humoral immune response during which short-lived plasma cells actively secrete pathogen-specific antibodies until the antigen is eliminated (24).…”
Section: Main Textsupporting
confidence: 93%
See 1 more Smart Citation
“…However, the most striking observation comes from the comparison of the 3 rd and 4 th quartile (70 to 84 and 85 to 114 days after symptoms onset, respectively), where a marked decrease in the mean OD values (significative mean OD decrease of -0.486 from 1.321 ± 0.720 to 0.835 ± 0.670, representing a 36.8% decrease with p-value of 0.0052) and an even more pronounced decrease in median values (median OD decreases from 1.411 (IQR 1.52) to 0.411 (IQR 1.15) representing a 70.1% decrease) were observed. Altogether, these observations are in agreement with recent studies reporting a decrease in anti-RBD responses and neutralization activity in the plasma of convalescent donors a few weeks after symptoms resolution (19)(20)(21)(22) Interestingly, the decrease in mean and median OD values during a period of about 20 days (considering the mean and median of 3 rd and 4 th quartiles, both of 76 and 95 days respectively) is reminiscent of the plasma IgG half-life of 21 days (23), suggesting that de novo synthesis of anti-RBD antibodies stopped between the 3 rd and 4 th quartiles in all CCP donors. This time frame is consistent with the first wave of a humoral immune response during which short-lived plasma cells actively secrete pathogen-specific antibodies until the antigen is eliminated (24).…”
Section: Main Textsupporting
confidence: 93%
“…The presence of antibodies against SARS-CoV-2 RBD was determined using a semi-quantitative ELISA. The assay was adapted from a recently described protocol (20,21). The plasmid encoding for SARS-CoV-2 S RBD was synthesized commercially (Genscript).…”
Section: Sars-cov-2 Rbd Elisamentioning
confidence: 99%
“…We first evaluated the presence of RBD-specific IgG and IgM antibodies by ELISA as we recently described (14). In agreement with a recent report (16), we observed that both RBDspecific IgG and IgM titers significantly decreased between 6 and 10 weeks after symptoms onset.…”
Section: Main Textsupporting
confidence: 83%
“…Moreover, in a cross-sectional study we reported that the neutralization capacity decreased between the third and the sixth week after symptoms onset (14). Since convalescent patients are generally required to wait for 14 days after recovery to start plasma donations and that they may give multiple times in the following weeks, most donations are likely to occur even later than this.…”
Section: Main Textmentioning
confidence: 95%
See 1 more Smart Citation